East Asian International Student Experiences as Learners of English as an Additional Language: Implications for School Counsellors - Popadiuk, Natalee E.; Marshall, Steve (Canadian Journal of Counselling and Psychotherapy, 2011)
In the school counselling literature, little focus is placed on international students who are learners of English as an Additional Language (EAL) and on school counselling support related to their language acquisition. Using the Critical Incident Technique, we analyzed transcripts of 21 international EAL students from China, Japan, and Korea who studied in three Vancouver, BC, public secondary schools. We present four language-based categories that include both facilitating and hindering incidents: (a) learning English, (b) communicating effectively, (c) speaking first language, and (d) performing well academically. Finally, we address school counselling implications, limitations, and future research.